Molecular Epidemiology, Antifungal Susceptibility, and Virulence Evaluation of Candida Isolates Causing Invasive Infection in a Tertiary Care Teaching Hospital - Chen, Junzhu; Hu, Niya; Xu, Hongzhi; Liu, Qiong; Yu, Xiaomin; Zhang, Yuping; Huang, Yongcheng; Tan, Junjun; Huang, Xiaotian; Zeng, Lingbing (Frontiers in Cellular and Infection Microbiology, 2021)
Background: The incidence of invasive candidiasis is increasing worldwide. However, the epidemiology, antifungal susceptibility, and virulence of Candida spp. in most hospitals remain unclear. Methods: MALDI-TOF and 18S rDNA ITS sequencing were used to identify Candida strains. Randomly amplified polymorphic DNA analysis was used for molecular typing. Biofilm production, caseinase, and hemolysin activities were used to evaluate virulence. The SensititreTM YeastOne YO10 panel was used to examine antifungal susceptibility. Sequencing for ERG11 and the hotspot regions of FKS1 of drug-resistant strains were used for evaluating the possible mechanisms of antifungal resistance. Results: We obtained 110 Candida strains, including 40 Candida albicans (36.36%), 37 C. parapsilosis (33.64%), 21 C. tropicalis (19.09%), 9 C. glabrata (8.18%), 2 C. rugose (1.82%), and 1 C. haemulonii (0.91%). At a limiting point of 0.80, C. albicans isolates could be grouped into five clusters, seven clusters for C. parapsilosis and C. tropicalis, and only one cluster for six C. glabrata isolates. Antifungal susceptibility testing revealed that the isolates showed the greatest overall resistance against fluconazole (6.36%), followed by voriconazole (4.55%). All C. albicans and C. parapsilosis isolates exhibited 100% susceptibility to echinocandins, whereas one C. glabrata strain was resistant to echinocandins. The most common amino acid substitutions noted in our study was 132aa (Y132H, Y132F) in the azole-resistant strains. No missense mutation was identified in the hotpot regions of FKS1. Comparison of the selected virulence tests, revealed that most Candida isolates were caseinase and hemolysin producers with a strong activity (Pz < 0.69). Furthermore, C. parapsilosis had greater total biofilm biomass (average Abs620 = 0.712) than C. albicans (average Abs620 = 0.214, p < 0.01) or C. tropicalis (average Abs620 = 0.450, p < 0.05), although all C. glabrata strains were either low- or non-biofilm producers. The virulence of the isolates from different specimen sources or clusters showed no obvious correlation. Conclusion: This study provides vital information regarding the epidemiology, pathogenicity, and antifungal susceptibility of Candida spp. in patients admitted to Nanchang City Hospital.